Pemenuhan Hak Anak Korban Perceraian Berdasarkan Hukum Positif Indonesia (Studi Kasus: Kasus Kabupaten Agam) - Moody Rizqy Syailendra; Eunike Kathryn Budiman; Desi i (Jurnal Ilmiah Wahana Pendidikan, 2023)
Humans cannot live alone because they are social beings, which means they need other living things. in order to fulfill his life well and also healthy in body. So then since birth humans have been referred to as social beings. This research contains efforts to fulfill the rights of children victims of divorce from both parents which is intended to find out how to fulfill children's rights after a divorce. The research methodology used in this study is a normative juridical approach that is doctrinal or doctrinal, using bibliography or document study. The results of the research All couples definitely want a harmonious and eternal household life. However, when there are many problems that arise in the household, not a few couples choose to end their household by divorce. Divorce that occurs will raise several problems, especially if the couple has become parents.